Glycemic index: a quality parameter of rice and its impact on rice consumers - Ghritlahre, S. K.; Kumar, Awadhesh; Yadav, M. K.; Aravindan, S (Indian Farming, 2018)
To follow a meal plan that is tailored to personal preferences and life style and helps in achieving goals for blood glucose, cholesterol and triglycerides levels, blood pressure, and weight management. Rice is high in carbohydrates which are needed for energy. Those with high physical activity like sports persons require carbohydrates. But if a person leads a lazy lifestyle without much physical exercise, high energy isn’t required and hence rice consumption should be reduced.